Whose internet is it anyway? Exploring adults' (non)use of the internet in everyday life - Selwyn, N; Gorard, S; Furlong, J (2005)
It is acknowledged that communication researchers need to develop more sophisticated and nuanced accounts of the social and individual dynamics of the internet in everyday life. Based on a household survey of 1001 adults with 100 in-depth follow-up interviews, the present article explores people's (non)use of the internet by asking: (1) who is (and who is not) using the internet in everyday life; (2) for what purposes people are using the internet and how are they developing their own constructions of the internet; and (3) how these understandings and uses of the internet are shaped by existing socioeconomic factors and circumstances. From this basis the article goes on to identify the key issues underlying adults' (non)use of the internet in terms of interest, relevance, mediation of significant others and the role of household dynamics. It also considers, from this basis, how non-users may be encouraged to make use of the internet.